Guerrilla gardening as normalised law-breaking: challenges to land ownership and aesthetic order - Millie, Andrew (Crime, media, culture, 2023)
This article considers guerrilla gardening that involves taking on other people’s land for gardening, usually without their permission. It is a practice that is overlooked largely by criminology, yet it can tell us something about attitudes to law and land ownership and challenges the approved aesthetic order of where we live. It can soften the look and feel of the city, leading to a different emotional and affective interaction with urbanity. Evidence is presented from a qualitative study of guerrilla gardeners from the North West of England. The discussion is informed theoretically by work on aesthetic criminology, do-it-yourself and temporary urbanism and the idea of urban commons. In this study, guerrilla gardening is found to be a normalised form of law-breaking that, despite not necessarily being to everyone’s taste and the gardeners having an autocratic view of property, is a form of urban intervention that is broadly accepted and welcomed, even by those who enforce the law.